Inappropriate Medication Prescriptions among Elders Surviving an Intensive Care Unit (ICU) Hospitalization - Morandi, A (2013)
BACKGROUND: Elderly patients admitted to intensive care units (ICU) are at risk of receiving potentially (PIMs) and actually inappropriate medications (AIMs). OBJECTIVES: To determine types of PIMs and AIMs, which PIMs are most likely to be considered AIMs, and risk factors for PIMs and AIMs at hospital discharge in elderly ICU survivors. DESIGN: Prospective cohort study SETTING: Tertiary care, academic medical center PARTICIPANTS: 120 patients ≥ 60 years old who survived an ICU hospitalization MEASUREMENTS: PIMs were defined according to published criteria; AIMs were adjudicated by a multidisciplinary panel. Medication lists were abstracted at the time of pre-admission, ward admission, Intensive Care Unit (ICU) admission, ICU discharge, and hospital discharge. Poisson regression was used to examine independent risk factors for hospital discharge PIMs and AIMs. RESULTS: Of 250 PIMs prescribed at discharge, the most common were opioids (28%), anticholinergics (24%), antidepressants (12%), and drugs causing orthostasis (8%). The three most common AIMs were anticholinergics (37%), non-benzodiazepine hypnotics (14%), and opioids (12%). Overall, 36% of discharge PIMs were classified as AIMs, but the percentage varied by drug type. Whereas only 16% of opioids, 23% of antidepressants, and 10% of drugs causing orthostasis were classified as AIMs; 55% of anticholinergics, 71% of atypical antipyschotics, 67% of non-benzodiazepine hypnotics and benzodiazepines, and 100% of muscle relaxants were deemed AIMs. The majority of PIMs and AIMs were first prescribed in the ICU. Pre-admission PIMs, discharge to somewhere other than home, and discharge from a surgical service predicted number of discharge PIMs, but none of the factors predicted AIMs at discharge. CONCLUSIONS: Certain types of PIMs, which are commonly initiated in the ICU, are more frequently considered inappropriate upon clinical review. Efforts to reduce AIMs in elderly ICU survivors should target these specific classes of medications.